Possibilities of Nursing High Education in the Context of COVID-19 - Reality and Perspectives - Manana Machitidze (European Scientific Journal, ESJ, 2022)
Aim/objective: The Covid-19 pandemic has swept the world and affected our daily life in various ways. While this impact is often negative, it has pushed some areas for development, overcoming challenges, and generating new opportunities. This article reviews the problem, its triggers, consequences, and perspectives. Background: The education sector faced a challenge at the beginning of the pandemic of maintaining security and high-quality teaching simultaneously, especially since there was no online teaching experience. Healthcare faculties were at the forefront of such difficulties, as the training included not only theoretical but also simulation and practical teaching, the implementation of which was initially unimaginable. Design and Methods: The article reviews and describes the global situation through secondary data analyses published in SCOPUS and PubMed from 2020-2022. Also, an analysis of survey results conducting in May 2020 at the University of Georgia (UG) School of Health Sciences. Results and Conclusions: To formulate the main difficulties will be taken list: teaching, research, and communication. Along with education, the challenge was increasing Internet usage, which in many cases led to delays in the teaching-learning process. Creating virtual platforms and developing online pedagogy is undoubtedly a significant pandemic challenge.